Pressure-induced instability in CdO - Aidouni, Ahmed Amine; Zaoui, A.; Ferhat, M. (physica status solidi (b), 2014)
The lattice dynamics of rocksalt CdO is studied as a function of pressure using density-functional linear-response theory. The predicted static phase-transition pressure from rocksalt (B1) to CsCl (B2) structures is 76.12 GPa. Analysis of the phonon calculations suggests that the pressure-induced instabilities at p = 78.26 GPa of the transverse acoustic (TA) modes in a large portion of the Brillouin zone are responsible for the phase transition from B1 → B2 phases of CdO. Moreover, the calculated partial phonon density of states at the precursor phase transition of p = 70 GPa reveals strong reduction of the longitudinal acoustic Cd-like modes and the existence of a large peak related to the longitudinal optic O-like mode.